Mineralogy, Geochemistry and Reserves Estimation of Lateritic Bauxite by Using Geostatistics: A case study at Daknong Province, Vietnam - , LUONG KIM NGAN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Daknong province located in central highland of Viet Nam where is predicted contains large tonnage of bauxite. Promote exploration and exploitation of bauxite and alumina production, Viet Nam will early development of the bauxite and alumina industry in Viet Nam as an opportunity to build more pillars for the country economy. The purposes of this study are to understand mineralogy, geochemistry of bauxite and calculating bauxite tonnage accurately, quickly and effectively by applying geostatistics methods and using software GS+, ArcGIS in a small area in Daknong province. Geostatistics provides descriptive tools such as variogram model, the spatial pattern of continuous and categorical samples for bauxite mining. Various interpolation kriging techniques capitalize on the spatial correlation between observations to predict attribute values at unsampled locations by using information related to one or several attributes at sampled locations. The data which are collected in this research include 367 hole and pit data (geological logs, assay data), 5 rock samples for thin section analysis, 3 bauxite samples for SEM analysis and 4 samples for XRF analysis and boundary of study area. All data are used to interpret mineralogy, geochemistry of host rock, bauxite and calculating bauxite tonnage. The result of analysis shows that the host rock of lateritic bauxite in Daknong Province is olivine basalt, the mineral component in lateritic bauxite as follow: gibbsite, goethite, clay minerals, carbonate minerals, quartz and ilmenite, limonite, quartz. The average chemical constituents of lateritic bauxite are 51% Al2O3, 15% Fe2O3, 2.5% SiO2, 2.3% TiO2 and LOI 27%. Using GS+ software to determine the variogram model of thickness, recovery value and grade of bauxite in accordance with the spatial distribution rule of lateritic bauxite in the study area and interpolate parameters by kriging method and check the performances of the interpolation methods by âleave one outâ cross validation, the error estimation between true value and estimate value are less than 4%. Finally, estimate the reserves of bauxite and alumina in the study area by using ArcGis with cut off grade of 40% Al2O3, 7% SiO2 and 25% recovery value give us the tonnage of bauxite are 6,797,466 tons and the tonnage of aluminum oxide are 3,471,019 tons.